Chapter La comunità dei predicatori e la lotta contro i catari. Un caso d'uso del video a 360° nelle Digital Humanities - Gagliardi, Isabella (Studi e saggi, 2022)
The chapter presents the case of the use of 360° video in the Digital Humanities and specifically in a lesson of the course in Historical Sciences. The 360° video provides students with both theoretical and experiential contextual information in situ. It begins with the view of Piazza Santa Maria Novella in Florence (the place of the oldest settlement of the Friars Preachers in Florence and their fight against the Cathars), then it moves to the cloister to reach the Dominican Library and then to read two pages of an illuminated choral. The 360 ​​° video was enriched with interactive points and enjoyed by the students in a laboratory equipped with HMD. The technological and didactic solutions adopted as well as the challenges faced and related solutions are illustrated, together with some recommendations.